Molecular characterization of cannabinoids and free fatty acid receptors in human and rat skeletal muscle - Shermado, Fairouz M. (2014)
The mechanisms underlying the development of insulin resistance in skeletal muscle are very complex and are not completely understood. Insulin resistance in skeletal muscle is of particular importance because muscle is the major site of insulin stimulated glucose uptake. Skeletal muscle is one of the major insulin sensitive organs and it is responsible for 80% of insulin stimulated glucose disposal as well as fatty acid oxidation. Elevated circulating free fatty acids (FFAs) and their derivatives such as endocannabinoids (ECs) have been described in obesity and are thought to be influential in the development of muscle insulin resistance. While several hypotheses have been put forward to explain the mechanisms by which FFAs and ECs may cause insulin resistance, there are still many potential signalling pathways which may be involved that have not yet been examined. The main aim of this thesis was to characterize the role of the cannabinoid receptors and free fatty acid receptor 1 (GPR40) in cell signalling in human and rat skeletal muscle tissue and primary cultured myotubes. Gene expression profiling of human skeletal muscle and cultured myotubes and myoblasts indicated that the cannabinoid receptor CB1 and GPR40 were expressed at low levels and these results were confirmed using Taqman QRTPCR. CB2 receptor expression was only detected in rat tissue and as a result was not further studied in cell culture systems. When global gene expression profiles were further examined it was evident that whilst cultured myotubes retained many characteristics of skeletal muscle tissue, the phenotype appeared to be closer to fetal than adult muscle. Furthermore, when metabolic gene expression networks were analysed using pathway based analysis, it was apparent that expression of genes involved in oxidative phosphorylation, insulin signalling and glucose transport were markedly reduced in cultured cells. The most striking example being GLUT4 which was expressed at approximately 3000-fold lower levels in cell culture as compared to tissue. The functionality of CB1 and GPR40 receptors was demonstrated using selective agonists and antagonists. CB1 activation by both synthetic and endogenous ligands was confirmed using phosphorylation of ERK1 and 2 as was the presence of functional GPR40 protein in myotubes. Neither agonists nor antagonists of CB1 or GPR40 receptors were found to modulate insulin signalling as determined by phosphorylation of downstream targets Akt and GSK3alpha/beta. Global expression profiling was also carried out on myotubes treated with GPR40 agonists and antagonists obtained from AstraZeneca. No changes in metabolic or insulin signalling genes were observed. Rather, antagonists of GPR40 appear to activate gene expression networks involved in cell proliferation – in particular an elevation in the ERBB2 signalling pathway.